1996
DOI: 10.1002/(sici)1097-0029(19960801)34:5<422::aid-jemt2>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and pathological changes at the node and paranode in human sural nerves

Abstract: The nodes and paranodes of peripheral nerve fibers are complex structures that are especially prone to artificial and pathological changes which have to be distinguished from normal developmental changes. Alterations during normal development are mainly caused by an increase in axonal diameter and myelin sheath thickness. The nodal, and paranodal axon diameters in human sural nerves reach their adult values at 3–5 years of age, simultaneously to the internodal diameter. The ratio between internodal and paranod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Sural nerve biopsies, performed when Patient PN‐44.1 was 40 years of age and when Patient PN‐761.3 was 3 years of age, were analyzed according to standard morphological procedures for light and electron microscopy 13…”
Section: Methodsmentioning
confidence: 99%
“…Sural nerve biopsies, performed when Patient PN‐44.1 was 40 years of age and when Patient PN‐761.3 was 3 years of age, were analyzed according to standard morphological procedures for light and electron microscopy 13…”
Section: Methodsmentioning
confidence: 99%
“…They concluded that the myelin attenuation occurring around axonal spheroids (axonal degeneration) resulted from mechanical slippage of the paranodal myelin . The paranode is the main anchorage point of the myelin lamellae to the axon, and mechanical myelin slippage is a well‐recognized consequence of paranodal pathology …”
Section: Classification Of Rlnmentioning
confidence: 99%
“…53 The paranode is the main anchorage point of the myelin lamellae to the axon, and mechanical myelin slippage is a well-recognized consequence of paranodal pathology. [67][68][69] When sural nerve biopsy specimen from human patients with a demyelinating polyneuropathy were compared to those with a primary axonal polyneuropathy (diagnosed on electrophysiological tests), there There is obvious loss of large myelinated nerve fibers (dotted arrow) in the affected horse (right) compared with the unaffected horse (left), and also note the increased subperineurial space and endoneurial connective tissue present in the section from the affected horse. A Renaut Body is highlighted by a solid black arrow in the normal horse.…”
Section: Tures Common Additional Pathological Changes Affecting the mentioning
confidence: 99%
“…At this site, the nerve has penetrated the fascia, can be relatively easily excised beneath the fatty tissue, and shows the fewest variations concerning number of fascicles and nerve fibres. There are usually 9-16 fascicles and in adults approximately 4,600-14,000 myelinated and 19,000-68,000 unmyelinated nerve fibres per mm 2 , depending on the age of the patient [13,17,32,35,36].…”
Section: Selection Of a Peripheral Nerve For Biopsymentioning
confidence: 99%
“…In borderline cases between pathologic and age-dependent "normal" changes, application of morphometry may be essential. The results of morphometric evaluation of control nerves from different periods of life are available from only a relatively small number of biopsy and autopsy studies (for references see [11,17,28,29,32,36]). …”
Section: Morphometrymentioning
confidence: 99%